Presence in time: watching live and recorded sports in VR increases spatial, interpersonal, and temporal presence - Frewen, Paul; Vincent, Andrew (Frontiers in Virtual Reality, 2024)
Introduction: Little research has explored the experience of viewing sporting events in threedimensional (3D) virtual reality (VR), whether at the time the sporting events are happening or at a later date.Participants (n = 148) were university students who watched brief segments of a 360° live stream of collegiate volleyball and basketball games, either live, at the time the games were happening, or approximately one week later. Participants watched segments of gameplay both while wearing and not wearing a 3D-VR headset, and provided spatial, interpersonal, and temporal presence ratings immediately afterward, as well as ratings of satisfaction with each viewing format.Results: Viewing the games in 3D-VR, as compared to watching the games on a standard twodimensional (2D) tablet computer, was associated with greater spatial, interpersonal, and temporal presence, and watching games live was associated with greater temporal presence. Although no differences were seen in overall satisfaction between the 3D-VR and standard 2D-tablet viewing formats, the more participants experienced a sense of presence while watching the games, the more they were satisfied with their sports viewing experience.Discussion: Sports spectatorship in 3D-VR is associated with a heightening of the feeling of spatial presence ("being there"), interpersonal (i.e., social) presence ("being together"), and temporal presence ("this is happening now"), regardless of whether the games that one is watching are actually occurring in the present, or are instead camera recordings that were captured sometime in the past. Researching the experience of temporal presence in response to recordings of other kinds of public (e.g., music concert) and private events (e.g., family memory) is recommended.